Можливість використання концепції колориметричних функцій у прикладних дослідженнях - Ярмак, І. М. (ХНУРЕ, 2020)
The results of the possibility of using the concept of colorimetric function in solving the problem of analysis of optical characteristics give different phenomena materials and media. The possibility of studying the temperature shows the distribution of pulsed plasma discharges. The example of optical coherence tomography shows that the colorimetric function provides the function of spectral analysis of the optical properties of the sample .
Keywords: колориметрична функція; оптична когерентна томографія